Autonomous sensory Meridian response as a physically felt signature of positive and negative emotions - Leung, Wai Lam; Romano, Daniela M. (Frontiers in Psychology, 2024)
Current research on Autonomous Sensory Meridian Response (ASMR) assumes that ASMR is always accompanied by contentment, and it is distinct from frisson due to such positive emotion. Thus, research investigations tend to limit their scope to solely focusing on the sensation of relaxation. This study explores whether it is possible to have a different emotional experience and still perceive ASMR, testing the theory of ASMR as an amplifier of pre-existing emotion instead of a determination of positive affect. The emotional arousal and valence, mood changes of 180 ASMR-capable and incapable individuals were analysed, using questionnaires, after altering the affective interpretation associated with auditory ASMR (tapping) with visual priming, to examine whether the primed emotion (fearful, relaxing, or neutral) could be amplified. It was found that an ASMR response occurred in all priming conditions, including the fear priming group, and the ASMR intensity demonstrated significant positive correlations with arousal in all conditions. No significant difference was found in the emotional outcome or mood of the neutral and relaxing priming groups. Upon comparison with ASMR-incapable individuals, both the relaxing and neutral priming groups demonstrated the same affect but greater potent for ASMR-capable. Individuals who appraised ASMR after visual fear priming demonstrated a significant decrease in positive emotional valence and increased arousal. The findings suggest that ASMR occurs in both positive and negative emotional situations, suppressing contentment induction if ASMR stimuli are interpreted negatively, and amplifying contentment when the stimuli are interpreted positively. While more research is needed, the results highlight that ASMR and frisson might be describing the same phenomenon, being both a physically felt signature of emotion. Therapeutic usage of ASMR should carefully select appropriate stimuli that emphasise contentment to avoid potential health risks associated with negative emotions until a further understanding of ASMR’s affective parameters has been established.